PERAN BUKU KOMIK DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Suparmi, Suparmi; Rahmawati, Putri; Widakdo, Ridwan; Gusparenady, Rachel Calista; Fathina, Rafa Azzahra (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
Students face various challenges in improving the quality and success of learning. Thus, a strong learning motivation factor is needed so that students are able to face learning challenges. The use of comic book media is one way to encourage students' interest in learning. The use of comic books as a learning medium has been widely implemented and the results have been proven to increase students' motivation to learn. The method used is in the form of literature study by searching, combining, and reviewing publications according to the topic of discussion. Data was taken from google scholar with the keyword